Thomas & friends Blue Mountain mystery - Tiernan, Greg; Sherman, Martin T.; Shale, Kerry; Hope, William, 1955-; Awdry, W. (New York, NY : Hit Entertainment, 2012)
Thomas investigates what Luke, a small green engine, did in his past that causes him to hide at the quarry.
Based on the stories by Rev. W. Awdry.
Features: Blue Mountain hide & peep game; learn about standard & narrow gauge engines; Blue Mountain mystery karaoke music video; Working together karaoke music video.
Voices: Martin T. Sherman, Kerry Shale, William Hope, Michael Brandon.
Originally broadcast on television in 2012.
MPAA rating: Not rated.
Blu-ray disc, DTS HD-MA 5.1.
Keywords: Awdry, W. -- Television adaptations; Thomas the Tank Engine (Fictitious character) -- Juvenile films; Friendship -- Juvenile films; Conduct of life -- Juvenile films; Quarries and quarrying -- Juvenile films; Thomas the Tank Engine (Fictitious character) -- Drama; Friendship -- Drama; Conduct of life -- Drama; Quarries and quarrying -- Drama; Children's television programs; Television series; Fiction television programs; Video recordings for the hearing impaired; Based on the book; Animated television programs